Tragic Echoes and Cries Multiplied: Notes for a Production of Vincent Woods’ Version of the Deirdre Story by Cia Ludens - Nunez, Domingos (ABEI Journal, 2011)
Since its foundation in 2003, the Brazilian theatre company, Cia Ludens, has produced four plays by outstanding Irish dramatists: Brian Friel,Marie Jones and Bernard Shaw. During this period, research into Irish drama and history was done as part of the process of staging these plays. Three cycles of staged readings and the publication of translated short plays by Shaw were conceived to illustrate part of the material investigated for the major productions. The result has been a stimulating dialogue between past and present, text and vocal/gestural possibilities and, above all, Irish and Brazilian cultures. The continuation of such a dialogue is the ongoing process of producing A Cry from Heaven by Vincent Woods. The aim of this article is therefore to give an account of the multiple aspects considered for the production of the play byCia Ludens, from the translation of the script into Portuguese and a study of tragedy up to the non-realistic conceptions for the staging of the text.